2019
DOI: 10.1111/tmi.13220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a maternal and newborn health system quality improvement project on the use of facilities for childbirth: a cluster‐randomised study in rural Tanzania

Abstract: Objectives: Reduction in maternal and newborn mortality requires that women deliver in high quality health facilities. However, many facilities provide sub-optimal quality of care, which may be a reason for less than universal facility utilization. We assessed the impact of a quality improvement project on facility utilization for childbirth. Methods: In this cluster-randomized experiment in four rural districts in Tanzania, 12 primary care clinics and their catchment areas received a quality improvement int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…One of the large-scale cluster randomized controlled trials on the effect of the implementation of WHO’s Safer Birth Checklist on quality of care and birth outcome, using external facilitators in a healthcare facility in India, showed improvement in the intrapartum care in the intervention area but did not show changes in maternal and perinatal mortality [37]. In a cluster-randomized trial in 12 rural primary care centers in Tanzania, a QI intervention (training, mentoring, infrastructure support, and peer outreach) improved quality antenatal care [38]. A multicountry observational study showed that rapid scale-up of training of neonatal resuscitation was associated with improvement in overall neonatal resuscitation practice [39] and improvement in perinatal mortality in a subset of the population [40].…”
Section: Discussionmentioning
confidence: 99%
“…One of the large-scale cluster randomized controlled trials on the effect of the implementation of WHO’s Safer Birth Checklist on quality of care and birth outcome, using external facilitators in a healthcare facility in India, showed improvement in the intrapartum care in the intervention area but did not show changes in maternal and perinatal mortality [37]. In a cluster-randomized trial in 12 rural primary care centers in Tanzania, a QI intervention (training, mentoring, infrastructure support, and peer outreach) improved quality antenatal care [38]. A multicountry observational study showed that rapid scale-up of training of neonatal resuscitation was associated with improvement in overall neonatal resuscitation practice [39] and improvement in perinatal mortality in a subset of the population [40].…”
Section: Discussionmentioning
confidence: 99%
“…No significant effect on women’s perceptions of technical care, quality of amenities, and interpersonal relations for any of the three sets of services observed (ANC, L&D, and PNC); increased the proportion of women reporting to have received medications/treatment during childbirth. Qualitative interviews: most women reported improved health service provision as a result of the intervention; drugs, equipment, and supplies were readily available due to the RBF4MNH; instances of neglect, disrespect, and verbal abuse during the process of care; increased workload resulting from an increased number of women seeking services at RBF4MNH facilities Moderate Larson et al (2019) [ 47 ] Rural Tanzania In-service training; mentoring; supportive supervision; peer outreach 04 years Mid-level cadres Primary care (community-based and primary care clinics) A cluster-randomized study: baseline (2012) and end line (2016) household surveys in control and intervention catchments; difference-in-differences analysis (DiD) Total study population-DiD: improved quality of ANC/contents of ANC [Adjusted (A) RR: 1.64; 95% CI: 1.00–2.71]; perceived quality of ANC (ARR: 1.14; 95% CI: 0.88–1.47); perceived obstetric care quality at intervention facility (ARR: 1.13; 95% CI: 0.79–1.62); reduced payment for obstetric care at intervention facility (ARR: − 3.76; 95% CI: − 7.02 to − 0.49). Previous home births-DiD: improved quality of ANC/contents of ANC (ARR: 2.31; 95% CI: 1.44–3.71); improved perceived quality of ANC (ARR: 1.57; 95% CI: 1.07–2.31); perceived obstetric care quality at intervention facility (ARR: 1.12; 95% CI: 0.78–1.59); reduced payment for obstetric care at intervention facility (ARR: − 2.24; 95% CI -4.76—0.28) Selection: LR Performance: SC Attrition: LR Detection: LR Reporting: LR (Magge et al (2017) [ 45 ] Rwanda Monthly onsite, regular clinical mentorship and training on evidence-based life-saving maternal and newborn care; learning collaborative to build healthcare workers’ leadership in data utilization for continuous quality improvement (QI); mobilizing financial resources; procurement and distribution of essential equipment and supplies 18 months Nurses, community health supervisors, data officers, and health facility and district leadership Primary care (Community-based and health centres), and secondary care hospitals A retrospective case study using the quantitative method: pre–post intervention evaluation Pre- vs post-intervention: ≥ 4 ANC (23% vs 38%); 1st trimester ANC (23% vs 34%); pregnant women with premature rupture of membrane (PROM) treated with antibiotics (24% vs. 38%); pregnant women with preterm labour treated with corticosteroids (26% vs 75%); SPAB (87% vs. 95%); time to C-section in minutes [median, (IQR): 99 (50–195) vs. 72 (59–77)]; immediate skin-to-skin care after delivery (19% vs. 87%); newborns checked for danger signs within 24 h of birth (47% vs. 98%) …”
Section: Resultsmentioning
confidence: 99%
“…The included studies described interventions that had been implemented in a range of settings: primary care ( n = 13) [ 39 , 40 , 44 , 47 49 , 54 57 , 59 61 , 63 ], secondary care hospitals ( n = 1) [ 52 ], primary care, and secondary care hospitals ( n = 8) [ 41 43 , 45 , 46 , 50 , 53 , 58 ], primary care, and secondary and tertiary care hospitals ( n = 1) [ 51 ], and referral hospitals ( n = 1) [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women's beliefs about local health services quality were also associated with ANC4 + attendance and facility-based delivery, which underscores long-standing evidence that quality of health services is a main determinant of its use. (29,30) Within the emotional dimension, self-e cacy was a signi cant ideational domain associated with use ANC4 + attendance and facility-based delivery. We found that women who felt con dent that they could get to a facility for ANC or delivery were 2.5-and 3.4-times more likely to attend ANC4 + times or give birth in a facility than women who lacked such con dence.…”
Section: Discussionmentioning
confidence: 99%